2012
DOI: 10.1371/journal.pone.0034818
|View full text |Cite
|
Sign up to set email alerts
|

Airflow Dynamics of Coughing in Healthy Human Volunteers by Shadowgraph Imaging: An Aid to Aerosol Infection Control

Abstract: Cough airflow dynamics have been previously studied using a variety of experimental methods. In this study, real-time, non-invasive shadowgraph imaging was applied to obtain additional analyses of cough airflows produced by healthy volunteers. Twenty healthy volunteers (10 women, mean age 32.2±12.9 years; 10 men, mean age 25.3±2.5 years) were asked to cough freely, then into their sleeves (as per current US CDC recommendations) in this study to analyze cough airflow dynamics. For the 10 females (cases 1–10), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 20 publications
5
83
0
Order By: Relevance
“…A similar large difference is to be found in the reports of human subject studies. Tang et al found that the peak coughing speed was 5.0 m/s, which was very similar to the peak sneezing speed of 4.5 m/s . Some other studies reported a much higher peak coughing speed of 6‐22 m/s (>10 m/s on average), and even a very high sneezing speed, up to 100 m/s …”
Section: Thermofluid Boundary Conditions For Thermal Manikinsmentioning
confidence: 73%
“…A similar large difference is to be found in the reports of human subject studies. Tang et al found that the peak coughing speed was 5.0 m/s, which was very similar to the peak sneezing speed of 4.5 m/s . Some other studies reported a much higher peak coughing speed of 6‐22 m/s (>10 m/s on average), and even a very high sneezing speed, up to 100 m/s …”
Section: Thermofluid Boundary Conditions For Thermal Manikinsmentioning
confidence: 73%
“…The person whose breath is visualised stands in front of the mirror and images are obtained when refl ected light from the mirror is refracted to different degrees as it passes from the warmth of the mouth to the cooler surrounding air. 49 The image that results looks like the surface of the moon, billowing out in particular patterns. Measurements can be made of the breath cloud relating to distance travelled, exhaled velocity, expansion rate and direction of fl ow.…”
Section: Bridging the Epistemic Gap 2: Visualising Breathmentioning
confidence: 99%
“…Smokers may suffer from chronic obstructive pulmonary disease (COPD) so that their respiratory patterns may be different from non‐smokers (Decramer et al., ). Typically, a smoker may generate a larger volume of cough air than a non‐smoker (Tang et al., ). Therefore, this study recruited ‘healthy’ smokers who reported no COPD in their consent forms to minimize this influence, although the experimental results may still be somewhat biased.…”
Section: Limitationsmentioning
confidence: 99%
“…To avoid the influence of smokers as human subjects, Tang et al. proposed to use the real‐time schlieren and shadowgraph imaging method to visualize the exhaled airflow (Tang and Settles, ; Tang et al., , , , ). This method does not require the introduction of visualization media such as tobacco smoke.…”
Section: Limitationsmentioning
confidence: 99%